Effects of pretreatment and solution chemistry on solubility of rice‐straw phytoliths. Issue 3 (28th November 2013) - Ngoc Nguyen, Minh; Dultz, Stefan; Guggenberger, Georg
Abstract: Rice is a Si‐accumulator plant, whereby Si has physio‐chemical functions for plant growth. Its straw contains high shares of plant silica bodies, so‐called phytoliths, and can, when returned to the soil, be an important Si fertilizer. Release of Si from phytoliths into soil solution depends on many factors. In order to improve prognosis of availability and management of Si located in phytoliths, in this study we analyzed the effect of pretreatment of rice straw by dry and wet ashing and the soil‐solution composition on Si release. Dry ashing of rice straw was performed at 400°C, 600°C, and 800°C and wet ashing of the original straw and the sample from 400°C treatment with H2 O2 . To identify the impact of soil‐solution chemistry, Si release was measured on separated phytoliths in batch experiments at pH 2–10 and in presence of different cations (Na +, K +, Mg 2+, Ca 2+, Al 3+ ) and anions (Cl –, NO$ _3^- $, SO$ _4^{2-} $, acetate, oxalate, citrate) in the concentration range from 0.1 to 10 mmolc L –1 . After burning rice straw at 400°C, phytoliths and biochar were major compounds in the ash. At an electrolyte background of 0.01 molc L –1, Si released at pH 6.5 was one order of magnitude higher than at pH 3, where the zeta potential (ζ) was close to zero. Higher ionic strength tended to suppress Si release. The presence of cations increased ζ, indicating the neutralization of deprotonated Si‐O – sites. Monovalent cations suppressed Si release more strongly than bivalent ones. Neutralization of deprotonated Si‐O – sites by cations might accelerate polymerization, leading to smaller Si release in comparison with absences of electrolytes. Addition of Al 3+ resulted in charge reversal, indicating a very strong adsorption of Al 3+, and it is likely that Si‐O‐Al‐O‐Si bonds are formed which decrease Si release. The negative effect of anions on Si release in comparison with deionized H2 O might be due to an increase in ionic strength. The effect was more pronounced for organic anions than for inorganic ones. Burning of rice straw at low temperatures ( e.g., 400°C) appears suitable to provide silicon for rice in short term for the next growing season. High inputs of electrolytes with irrigation water and low pH with concomitant increase of Al 3+ in soil solution should be avoided in order to keep dissolution rate of phytoliths at an appropriate level.